Ambilaterality manifestation at junior female judokas in Tachi-Waza technique - Mostoflei, F.; Balnica. I. (Sport Science Review, 2010)
The total training process in judo at the junior level assumes in an essential way the improvement of specific psycho-motric qualities, the enlargement of technical support and competition experience. The present study is focused on a specific particularity of coordinative ability, namely on its manifestation considering the dominant laterality in imposed working conditions.